Optimization of the Distribution Chain of the Meat Marketing Sector through Facility Location Models - Cabrera, Javier; Araujo, Gabriela; Pesantez-Chica, Rosalba; Orellana-Quezada, Dalton (Journal of Ecohumanism, 2025)
Understanding marketing as a structural and functional system that manages the product at the moment it leaves the establishment until it reaches the consumer, it is necessary to have the objective of having optimal marketing places that integrate distance, production, and marketing costs, as well as variables. as the optimal location. In this sense, we start from the integration of optimal location models Weber, p-median, vehicle routing, and travel agent, achieving that, for the marketing of meat in the city of Azogues, by correlation of distances it must be carried out in the Recinto Ferial Market, achieving savings of 14.5% and from a cost reduction analysis of 7.9%, an optimal distribution route obtained. With these results, it is achievable to see the advantage of the Facility Location model; however, applying a complementary Cooperative Game Theory with transferable utility is proposed, strengthening the work in associativity, achieving even fewer plus losses by 15.3%.